The feelings book : the care & keeping of your emotions - Madison, Lynda; Bendell, Norm (Middleton, Wis. : Pleasant Co., 2002)
Discusses a variety of emotions girls might experience and suggests ways of dealing with them.
"American Girl library."
Ages 8 and up.
Keywords: Emotions in children -- Juvenile literature; Girls -- Psychology -- Juvenile literature; Emotions; Girls -- Psychology; Life skills